2021
DOI: 10.1002/smll.202006231
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Based Nanoscale Coordination Polymers Augmented Tumor Radioimmunotherapy for Immunogenic Cell Death Induction and T‐Cell Infiltration

Abstract: Insufficient T‐cell infiltration seriously hinders the efficacy of tumor immunotherapy. Induction of immunogenic cell death (ICD) is a potentially feasible approach to increase T‐cell infiltration. Since ionizing radiation can only induce low‐level ICD, this study constructs Cu‐based nanoscale coordination polymers (Cu‐NCPs) with mixed‐valence (Cu+/Cu2+), which can simultaneously and independently induce the generation of Cu+‐triggered hydroxyl radicals and Cu2+‐triggered GSH elimination, to synergize with rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 75 publications
0
47
0
2
Order By: Relevance
“…A recent study revealed that magnesium can promote CD8 T cell activation and high expression levels of PD-1 by regulating metabolic reprogramming to enhance the efficacy of immunotherapy ( Lötscher et al, 2022 ). In addition, some studies have shown that copper is related to T cell infiltration and recruitment ( Kaddatz et al, 2021 ; Wang et al, 2021 ). However, whether these cuproptosis-related genes can affect the immune characteristics of HCC remains largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study revealed that magnesium can promote CD8 T cell activation and high expression levels of PD-1 by regulating metabolic reprogramming to enhance the efficacy of immunotherapy ( Lötscher et al, 2022 ). In addition, some studies have shown that copper is related to T cell infiltration and recruitment ( Kaddatz et al, 2021 ; Wang et al, 2021 ). However, whether these cuproptosis-related genes can affect the immune characteristics of HCC remains largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…[180] This Cu + /Cu 2+ -based RT noticeably intensified the ICD effect, increased the population of matured DCs from 19.7% to 35.1% in lymph nodes (Figure 12e). Combined with anti-PD-L1 antibodies, the Cu-based nanostructure effectively inhibited the growth of distant tumors (Figure 12f) and promoted [180] Copyright 2021, Wiley-VCH.…”
Section: Icd By Radiotherapymentioning
confidence: 91%
“…CuSO 4 and 5′‐guanosine monophosphate (5′‐GMP) self‐assembled to prepare a mixed valence Cu + /Cu 2+ ‐based nanoscale coordination polymer ( Figure 12 a ), in which Cu + could decompose H 2 O 2 to •OH and Cu 2+ deplete GSH to GSSG (Figure 12b–d ). [ 180 ] This Cu + /Cu 2+ ‐based RT noticeably intensified the ICD effect, increased the population of matured DCs from 19.7% to 35.1% in lymph nodes (Figure 12e ). Combined with anti‐PD‐L1 antibodies, the Cu‐based nanostructure effectively inhibited the growth of distant tumors (Figure 12f ) and promoted intratumoral CD8 + T cells infiltration and IFN‐ γ secretion for potent immune responses (Figure 12g,h ).…”
Section: Icd Induced By Nddss In Combination With Immunotherapymentioning
confidence: 99%
“…Encouragingly, the coordination of Cu 2+ ions with organics is a feasible strategy to obtain Cu + ions. [ 22 ] Thus, we introduce Cu 2+ ions, in the precursors of ZIF‐90, Zn 2+ ions, and imidazol‐2‐carboxyaldehyde (2‐ICA), to prepare mixed‐metal Cu/Zn‐MOF at room temperature. Transmission electron microscopy (TEM) images of the Cu/Zn‐MOFs with different Cu contents demonstrated their sphere morphology with the size of ≈110, 210, and 120 nm derived from ZIF‐90 ( Figure a).…”
Section: Resultsmentioning
confidence: 99%